Cannabinoid Signaling in Kidney Disease - Liana Arceri; Thanh Khoa Nguyen; Shannon Gibson; Sophia Baker; Rebecca A. Wingert (Cells, 2023)
Endocannabinoid signaling plays crucial roles in human physiology in the function of multiple systems. The two cannabinoid receptors, CB1 and CB2, are cell membrane proteins that interact with both exogenous and endogenous bioactive lipid ligands, or endocannabinoids. Recent evidence has established that endocannabinoid signaling operates within the human kidney, as well as suggests the important role it plays in multiple renal pathologies. CB1, specifically, has been identified as the more prominent ECS receptor within the kidney, allowing us to place emphasis on this receptor. The activity of CB1 has been repeatedly shown to contribute to both diabetic and non-diabetic chronic kidney disease (CKD). Interestingly, recent reports of acute kidney injury (AKI) have been attributed to synthetic cannabinoid use. Therefore, the exploration of the ECS, its receptors, and its ligands can help provide better insight into new methods of treatment for a range of renal diseases. This review explores the endocannabinoid system, with a focus on its impacts within the healthy and diseased kidney.